Synthesis of 4-Arylquinazolines by Arylation of Quinazolin-4-ones under Mild Conditions - Qiu, Guanyinsheng; Huang, Ping; Yang, Qin; Lu, Hui; Xu, Jingshi; Deng, Zhihong; Zhang, Ming; Peng, Yiyuan (Synthesis, 2013)
An efficient route to 4-arylquinazolines via arylation of quinazolin-4-ones under mild condition is described. The reaction is carried out by the palladium-catalyzed coupling of quinazolin-4-ones with arylboronic acids in the presence of TsCl leading to 4-arylquinazolines in good to excellent yields.
Keywords: 4-arylquinazoline; arylation; arylboronic acid; quinazolin-4-one